Evaluating The Use Of An Interactive Multimedia Module For Music History Among Students - Lim, Mei Ling (2009)
In this research study, an interactive multimedia tool for learning music history was developed. The objective of this study was to integrate multimedia into the teaching and learning strategy in the classroom and to create a student-centred learning environment in order to enhance the students\' learning process.